White opportunity Should Russian Arctic activity be considered offensive or defensive? - Þórarinn Gunnarsson 1993- (2017)
In this paper, it is examined whether that the Russian decision to bolster their Arctic defenses as a new geographical reality concerning their Arctic borders threatens the security of other Arctic states. Furthermore, if it is rational for these neighboring states to fear these actions by the Russian Federation, as it gives the perception of decreased security for them. For this analysis, I used the Realist and the Liberal theories, two fundamental theories in International relations with much focus on the Security dilemma which was treated as a separate theory for the sake of the paper. The Arctic is a treasure chest filled with loot for nations and corporations to exploit. So, the Arctic recourses had to be looked at, their energy abundance and the problems assessing them. The Russian economy was analyzed briefly and their dependence on their energy sector for foreign currency and economic security. The hard security questions raised by the change in the Arctic. Arctic politics to get a sense of the Arctic region and the nature of the communications between Arctic nations.